A review of the spider genus Singaporemma (Araneae: Tetrablemmidae), with the description of a new species - Yan, Fanhu; Lin, Yucheng (Zootaxa, 2018)
The genus Singaporemma Shear, 1978, which currently includes seven species, is reviewed. In this study, we reexamine and photograph the type material of all the species. A new species, Singaporemma takensis sp. n. is documented as new to science and as the first record of the genus from Thailand. We provide a key to Singaporemma spp., based only on genital characters, along with diagnoses, illustrations and distribution map for all the species of Singaporemma.